2017
DOI: 10.1007/s11104-017-3424-5
|View full text |Cite
|
Sign up to set email alerts
|

Plant exudates improve the mechanical conditions for root penetration through compacted soils

Abstract: Background and aim Plant exudates greatly affect the physical behaviour of soil, but measurements of the impact of exudates on compression characteristics are missing. Our aim is to provide these data and explore how plant exudates may enhance the restructuring of compacted soils following cycles of wetting and drying. Methods Two soils were amended with Chia (Salvia hispanica) seed exudate at 5 concentrations, compacted in cores to 200 kPa stress (equivalent to tractor stress), equilibrated to −50 kPa matric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 46 publications
1
55
0
Order By: Relevance
“…Carminati et al () revealed the influence of mucilage on the water holding capacity of the soil immediately around the root, and its implications for hydraulic continuity around the root system was demonstrated by (Moradi et al, ). In compacted soils, the influence of plant derived exudates have been highlighted to improve mechanical conditions for root penetration (Oleghe, Naveed, Baggs, & Hallett, ). Carminati and Vetterlein () proposed the concept of rhizosphere plasticity to help understand the bimodal hydraulic responses found at the root–soil interface under different bulk soil moisture conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Carminati et al () revealed the influence of mucilage on the water holding capacity of the soil immediately around the root, and its implications for hydraulic continuity around the root system was demonstrated by (Moradi et al, ). In compacted soils, the influence of plant derived exudates have been highlighted to improve mechanical conditions for root penetration (Oleghe, Naveed, Baggs, & Hallett, ). Carminati and Vetterlein () proposed the concept of rhizosphere plasticity to help understand the bimodal hydraulic responses found at the root–soil interface under different bulk soil moisture conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[13] state that MRP values up to 2500 KPa are considered low and show little limitation on root development. High MRP values increase resistance to root growth [19], reduction in total soil porosity by reducing water storage and restriction of gas flow [20]. The large spatial variability of the mechanical resistance to penetration presents a series of implications for root and shoot growth [21].…”
Section: Resultsmentioning
confidence: 99%
“…Seed exudate was extracted from chia (Salvia sp.) by the same method described in Oleghe, et al (2017).…”
Section: Tablementioning
confidence: 99%
“…Gravimetric water content, water sorptivity and cone penetration measurements were repeated. The samples were then rewetted and dried again to -50 kPa, followed by compression to 600 kPa on the same mechanical test frame using approaches described in Oleghe et al (2017).…”
Section: Mechanical and Hydrological Measurementsmentioning
confidence: 99%